PERAN PEREMPUAN DALAM PEMBANGUNAN DI DESA DAYAH KEURAKO TAHUN 2009 HINGGA SEKARANG - Fazilah, Nurul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2025)
This study aims to examine the role of women in village development through the Family Welfare Empowerment (PKK) program in Dayah Keurako Village, Pidie Regency. Using a descriptive qualitative approach, data were collected through direct observation and document analysis to gain an in-depth understanding of how women participate as subjects, not merely objects, in development. The findings indicate that although women have historically been marginalized due to patriarchal cultural norms, gender mainstreaming policies have begun to open space for more active female participation. In Dayah Keurako, the PKK organization serves as a crucial platform for women to engage in various sectors such as health, education, economy, and socio-cultural activities. Progressive leadership such as that demonstrated by PKK chairwoman Nadariana has significantly improved the quality and involvement of female cadres. However, internal challenges such as the dual roles of women and lack of self-confidence remain obstacles. This study recommends enhancing training, promoting gender equality, and strengthening the capacity of village women to better position them as drivers of development. Keywords: women, village development, PKK, gender, women's participation